A systematic assessment of road pavement sustainability through a review of rating tools - Bryce, James; Brodie, Stefanie; Parry, Tony; Lo Presti, Davide (Elsevier, 2017)
Pavements are engineered systems present in every modern society, and they have significant environmental, economic and social impacts. In an effort to promote more sustainable decisions regarding pavement design, construction and management, several pavement sustainability assessment tools have been developed. This research reviewed some of these tools and found that many of them do not treat the pavement as a system; instead, they seek to optimize individual aspects of the pavement in an effort to increase its sustainability. Therefore, a framework for analytically assessing the system outcomes towards sustainable objectives is presented and applied for modern pavement sustainability assessment. The results suggest that this framework provides a way to systematically include data in the evaluation of the outcomes of pavement management decisions towards achieving sustainable objectives.